2014
DOI: 10.1002/jbmr.2374
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 Channels Are Essential for Normal Bone Structure and Osteocyte Viability

Abstract: Connexin (Cx) 43 serves important roles in bone function and development. Targeted deletion of Cx43 in osteoblasts or osteocytes leads to increased osteocyte apoptosis, osteoclast recruitment, and reduced biomechanical properties. Cx43 forms both gap junction channels and hemichannels, which mediate the communication between adjacent cells or between cell and extracellular environments, respectively. Two transgenic mouse models driven by a DMP1 promoter with the overexpression of dominant negative Cx43 mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 44 publications
3
116
2
2
Order By: Relevance
“…Up to 30% unoccupied osteocyte lacunae have been observed in cortical bone of Cx43 conditional knockout mice (Bivi et al, 2012a;Lloyd et al, 2014;Xu et al, 2015). Despite the nearly identical cortical bone phenotype observed in the Gja1 −/K258Stop and Cx43 conditional knockout models, we did not detect any difference in empty lacunae between groups, suggesting that osteocytic apoptosis does not precede the phenotype, at least in male Gja1 −/K258Stop mice.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Up to 30% unoccupied osteocyte lacunae have been observed in cortical bone of Cx43 conditional knockout mice (Bivi et al, 2012a;Lloyd et al, 2014;Xu et al, 2015). Despite the nearly identical cortical bone phenotype observed in the Gja1 −/K258Stop and Cx43 conditional knockout models, we did not detect any difference in empty lacunae between groups, suggesting that osteocytic apoptosis does not precede the phenotype, at least in male Gja1 −/K258Stop mice.…”
Section: Discussioncontrasting
confidence: 64%
“…4D). As osteocyte apoptosis has been implicated as one of the mechanisms of the effects of Cx43 on bone (Bivi et al, 2012a;Xu et al, 2015), empty and occupied osteocyte lacunae were counted in cortical bone for mice of each genotype. The percentage of occupied osteocyte lacunae was unaffected by Cx43 CT truncation (Fig.…”
Section: Altered Bone Formation Rates In Male Gja1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, other evidence suggests that inhibiting this communication can enhance bone formation during loading High-resolution 3D imaging of osteocyte anatomy and pathology and preserve it during unloading, which is reviewed by Lloyd and colleagues (2014). Recent studies have shown that the osteocyte gap junction channel Connexin 43 plays an integral role in bone mechanobiology and osteocyte viability (Plotkin et al, 2015;Riquelme et al, 2015;Xu et al, 2015). Primary cilia.…”
Section: Onandlcn At the Ultrastructural Levelmentioning
confidence: 99%
“…Recent studies have shown that the osteocyte gap junction channel Connexin 43 plays an integral role in bone mechanobiology and osteocyte viability (Plotkin et al, 2015;Riquelme et al, 2015;Xu et al, 2015). Primary cilia.…”
Section: Pm Goggin Et Almentioning
confidence: 99%